CROSS-NATIONAL MEASUREMENT INVARIANCE OF THE PATIENT HEALTH QUESTIONNAIRE-4 (PHQ-4) AS A SCREENING MEASURE FOR DEPRESSION AND ANXIETY SYMPTOMS IN 12 LATIN AMERICAN COUNTRIES - Caycho-Rodríguez, Tomás; Vilca, Lindsey W.; Ventura-León, José; Valencia, Pablo D.; Carbajal-León, Carlos; Reyes-Bossio, Mario; Delgado-Campusano, Mariel; Yupanqui-Lorenzo, Daniel E.; Rojas-Jara, Claudio; Gallegos, Miguel; Cervigni, Mauricio; Martino, Pablo; et al. (Psychological thought, 2024)
The Patient Health Questionnaire-4 (PHQ-4) is a widely used instrument to measure symptoms of depression and anxiety in general, but not much is known about its cross-cultural utility in Latin America. The present study evaluated the measurement invariance of the PHQ-4 in adult samples (N = 5441) from 12 Latin American countries (Paraguay, El Salvador, Chile, Ecuador, Colombia, Uruguay, Peru, Mexico, Cuba, Guatemala, Argentina, and Bolivia). The two-factor structure presented a superior fit to the one-factor structure. This provides evidence to support a two-dimensional model of anxious and depressive symptomatology of the PHQ-4, with a good estimate of reliability. The configural, metric, scalar and strict invariance of the PHQ-4 was supported, suggesting that participants from all countries attribute the same meaning to the latent constructs anxiety and depression and their scores can be compared. Additionally, support was provided for the hypothesis that the presence of depressive symptoms significantly predicts subjective well-being. However, the presence of anxiety symptoms fails to significantly predict participants well-being. It is concluded that the PHQ-4 provides a largely comparable measure of anxiety and depression symptoms in a large sample of Latin American countries.